Analysis of Lift and Drag of Mono-foil Hysucat due to Longitudinal Foil-placement Variation - Ketut Suastika; Regi Y. Dikantoro; Dedi B. Purwanto; Dony Setyawan; Wing H. A. Putra (International Journal of Marine Engineering Innovation and Research, 2018)
CFD simulations were conducted to study the effects of a hydrofoil and its relative placement in the longitudinal direction on the total resistance of a mono-foil hysucat (hydrofoil supported catamaran). Three foil positions were considered: (i) precisely below the vessel’s center of gravity, (ii) 3 chord-lengths aft from position 1 and (iii) 6 chord-lengths aft from position 1. At relatively low speed (volumetric Froude number FnV < 1.8), the hydrofoil results in an increase of the total resistance of the hysucat (up to 4.43%). At relatively high speed (FnV > 1.8), the hydrofoil results in a decrease of the total resistance (up to 34.86%). The resistance coefficient first increases, takes a maximum value and then decreases with increasing Froude number. The maximum value is observed at FnV approximately equal to 1.4 (or Fn approximately equal to 0.5), consistent with previous observations. The most optimum foil placement is that precisely below the center of gravity of the vessel.